Morphine and neurotransmitter substances: Microiontophoretic study in the rat brain stem - Bradley, P.B. (1974)
1 The effects of microiontophoretically applied morphine and its interactions with the effects of microiontophoretic applications of either acetylcholine, (-)-noradrenaline or 5-hydroxytryptamine have been studied on single neurones in the brain stem of rats anaesthetized with urethane. 2 Morphine excited or inhibited most neurones tested and the effects, especially excitation, were often extremely powerful. However, the time course of the excitatory and inhibitory effects were somewhat different. 3 Desensitization to the excitation produced by morphine was seen after repeated or prolonged applications and it is suggested that this phenomenon may be related to the tolerance which develops after chronic administration of morphine. No desensitization was observed to inhibition of neuronal activity by morphine. 4 Morphine usually reduced the excitation of neurones by acetylcholine, noradrenaline or 5-hydroxytryptamine but sometimes potentiated the effect, although not always on the same neurones. Inhibition of neuronal activity by these compounds was never modified by morphine and neither were the effects of glutamate or D,L-homocysteic acid when used as control agonists. 5 The in vitro release of morphine from six micropipettes was determined and the transport number was calculated to be 0.051 (s.d. 0.021). 6 The implications of these observations in explaining the pharmacological actions of morphine are discussed.